(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2018)
Background: Stroke rehabilitation is a program designed to help the stroke patients to overcome the disability. Few studies have evaluated the profile of stroke patients. To provide information about demographic data & disease pattern among the patients receiving stroke rehabilitation. Methods: A retrospective study was carried out in the Department of Physical Medicine and Rehabilitation (PMR), National Institute of Neuroscience and Hospital (NINSH) Dhaka, Bangladesh for the period of two year from 1st July 2013 to 30th June, 2015. Results: Total five thousand nine hundred thirty nine (n=5939) patients were studied, of which 62.33% were male and 37.67% were female. Maximum patients (27.93%) belong to 51-60 years of age. Major patients (52.67%) came from Dhaka city and most of the studied patients were housewife (25.43%). Largest disease group was ischaemic stroke (81.7%). Regarding service pattern, 69.59% patients received outdoor and 30.41% indoor services. Among clinical profile of stroke, 90.5% were first time onset, almost 99% suffered limb weakness, 24.03% speech problem and 32.6% face involvement. Maximum patients (58.8%) had history of multiple risk factors. Conclusion: Rehabilitation procedures in stroke patients can enable greater return of neurological functions and prevents complication, thereby improves long term outcome and quality of life. Chatt Maa Shi Hosp Med Coll J; Vol.17 (1); Jan 2018; Page 9-12